Acceleration of Amyloidosis by Inflammation in the Amyloid-Beta Marmoset Monkey Model of Alzheimer’s Disease - Philippens, Ingrid H. (J Alzheimers Dis, 2016)
Background: The immune system is increasingly mentioned as a potential target for Alzheimer’s disease (AD) treatment. Objective: In the present pilot study, the effect of (neuro)inflammation on amyloidopathy was investigated in the marmoset monkey, which has potential as an AD animal model due to its natural cerebral amyloidosis similar to humans. Methods: Six adult/aged marmosets (Callithrix jacchus) were intracranial injected with amyloid-beta (Aβ) fibrils at three cortical locations in the right hemisphere. Additionally, in half of the monkeys, lipopolysaccharide (LPS) was co-injected with the Aβ fibrils and injected in the other hemisphere without Aβ fibrils. The other three monkeys received phosphate buffered saline instead of LPS, as a control for the inflammatory state. The effect of inflammation on amyloidopathy was also investigated in an additional monkey that suffered from chronic inflammatory wasting syndrome. Mirror histology sections were analyzed to assess amyloidopathy and immune reaction, and peripheral blood for AD biomarker expression. Results: All LPS-injected monkeys showed an early AD immune blood cell expression profile on CD95 and CD45RA. Two out of three monkeys injected with Aβ and LPS and the additional monkey, suffering from chronic inflammation, developed plaques. None of the controls, injected with Aβ only, developed any plaques. Conclusion: This study shows the importance of immune modulation on the susceptibility for amyloidosis, a hallmark of AD, which offers new perspectives for disease modifying approaches in AD.